Endoloop-Assisted Polypectomy for a Symptomatic Giant Colonic Polyp in a Pediatric Patient - Yen-Chung Lin; Jen-Wei Chou; An-Chyi Chen; Shu-Fen Wu; Ching-Tien Peng; Walter Chen; Chien-Heng Lin (MDPI AG, 2022)
Colonic polyps are a common cause of persistent bloody stools in pediatric patients. Such polyps are easily diagnosed by a barium study of the lower gastrointestinal tract or by colonoscopy. Polypectomies utilizing electric ligators are generally performed on pediatric patients, and such patients can be easily operated on. However, giant colonic polyps have been reported in pediatric patients. In the past, a laparotomy or laparoscopy would have been performed in some pediatric patients diagnosed with a giant colonic polyp; however, the large size, location, or position of the polyp would sometimes be too large or the location or position of the polyp would make successful operation difficult. In general, larger stumps with large feeding arteries are associated with larger colonic polyps. Therefore, if such a polyp is removed via electric polypectomy alone, there may be a higher risk of post-polypectomy bleeding from its stump. We report a case of a 14-year-old male patient who presented with a 2-month history of bloody stools. A giant juvenile colonic polyp was detected by colonoscopy in the transverse colon. Finally, we successfully removed the giant polyp by using endoloop-assisted polypectomy.